Task-based learning module in teaching speaking to literacy and numeracy screening students - Izatil Aqmar Mohd Zamzam; Universiti Sultan Zainal Abidin . Faculty of Languages and Communication (2020)
English is taught as a second language in Malaysian primary and secondary schools. However, students have difficulties to speak English as it is not their native language. Many students were reported to have the ability to write well, but they failed in their speaking test due to lack of speaking ability in English. Previous studies showed that students faced many difficulties in practising the English language outside the classroom as they have less authentic chances to use the language. This study aims to examine the task-based module in teaching the speaking lessons to Literacy and Numeracy (LINUS) students of National School of Demit, Kelantan. This study employed a mixed-method approach to collect data. The sample was selected using purposive sampling, comprising 30 Year One students and two teachers, who were teaching Year One classes from National School of Demit in Kelantan. The research instruments used included the pre-test and post-test, focus group discussion and interviews with experienced teachers. The results showed the effectiveness of the taskbased learning module in assessing the speaking skill of the LINUS students. Majority of the students obtained high achievement in English subject, and their performances increased after learning through task-based speaking activities. The students were able to assist their friends during the activities, leading to collaborative learning indirectly. The findings also revealed that teachers have positive perceptions towards task-based learning method, as it was considered essential in ensuring the students to enhance their speaking skill effectively. During the implementation of the task-based learning lessons, the students' positive attitudes helped them succeed in completing the given tasks. The teachers' concerns of handling a big class were overcome when the results of the task-based learning were positive. Task-based learning methods have improved the achievement, performance and effectiveness of students' speaking skill. The study suggested that task-based learning module should be applied for teaching the new curriculum syllabus in Malaysian schools, known as Common European Framework (CEFR). This study contributed to teachers as a guide to carry out task-based learning in classroom to help students to master the listening and speaking skills.
1. Introduction -- 2. Literature review -- 3. Research methodology -- 4. Findings -- 5. Discussion of findings -- 6. Recommendation and conclusion
Thesis (Degree of Master of English Language Studies) - Universiti Sultan Zainal Abidin, 2020
Includes bibliographical references (leaves 188-197)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Languages and Communication -- Dissertations; Dissertations, Academic; English language -- Study and teaching -- Bilingual method; Language and languages -- Study and teaching; Second language acquisition; Task analysis in education